2008
DOI: 10.1097/mlg.0b013e31816dd2d9
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine/Lidocaine Injection Vs. Saline During Endoscopic Sinus Surgery

Abstract: Injection of epinephrine/lidocaine mixture does not produce higher blood levels of epinephrine when compared to saline injection and did not induce any harmful side effects. We postulate that the combination with lidocaine 1% may reduce the patients' stress and thus prevent higher catecholamine levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 20 publications
(38 reference statements)
2
67
0
2
Order By: Relevance
“…These levels were consistent with the values reported in the literature. 1,3,31 Multiple intrinsic and extrinsic factors, particularly the use of a general anesthetic, contribute to the final recorded blood pressure. However, the lack of significant hypertensive episodes noted in our cohort supports CE's lack of significant impact on systemic vascular parameters-a finding that is in concordance with our lack of complications.…”
Section: Discussionmentioning
confidence: 99%
“…These levels were consistent with the values reported in the literature. 1,3,31 Multiple intrinsic and extrinsic factors, particularly the use of a general anesthetic, contribute to the final recorded blood pressure. However, the lack of significant hypertensive episodes noted in our cohort supports CE's lack of significant impact on systemic vascular parameters-a finding that is in concordance with our lack of complications.…”
Section: Discussionmentioning
confidence: 99%
“…High doses of epinephrine and inadvertent intravenous injection have contrasting effects with life-threatening tachycardia and severe hypertension two well established consequences. Although a recent RCT by Cohen-Kerem et al [32] did show a benefit in the operative field when epinephrine infiltration was used compared to saline, a more recent similarly designed RCT by Javer et al [35] did not replicate these findings. In fact, in this study a statistically significant increase in MABP was noted in the epinephrine study arm, despite the absence of obvious intravenous infiltration.…”
Section: Local Infiltrationmentioning
confidence: 93%
“…Local infiltration with epinephrine containing local anesthetic agents is thought to improve hemostasis through both their local vasoconstrictor action as well as their anesthesia of nasal mucosa against surgical stimulation [32].…”
Section: Local Infiltrationmentioning
confidence: 99%
“…Hemostatic efficacy of local anesthetic with vasoconstrictor was demonstrated in a study that showed decreased bleeding when lidocaine/epinephrine was injected as compared to injection of placebo ( P < 0.05) [39]. However, intraoperative estimated blood loss was not significantly different between the anesthetic/epinephrine and control groups ( P > 0.05) [29, 30].…”
Section: Surgical Considerationsmentioning
confidence: 99%
“…Arterial pressure and heart rate were affected immediately after injection of lidocaine/epinephrine but were not elevated over the normal range [39]. Another study found no significant difference between bupivacaine/epinephrine and control groups ( P > 0.05) [41].…”
Section: Surgical Considerationsmentioning
confidence: 99%